Walt Disney's Pinocchio - Grant, Campbell (New York : Golden Press, 1948)
A wooden puppet must earn the right to be a real boy by proving that he is brave, truthful, and unselfish.
"Based on the story by Collodi"
Keywords: Puppets -- Juvenile fiction; Fairy tales